Evaluation of the literacy and numeracy strengthening program in elementary schools of Kemantren Tegalrejo - Etik Setyaningsih; Nurtanio Agus Purwanto; Lantip Diat Prasojo; Firmansyah Firmansyah (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2025)
Literacy and numeracy skills are core competencies in determining students' acade-mic achievement and lifelong learning. Elementary schools in Tegalrejo District have implemented literacy and numeracy strengthening programs for the past two years. However, an evaluation of the program has not been conducted. Based on this, this study aims to evaluate the implementation of the literacy and numeracy strengthening program in nine elementary schools in Tegalrejo District using the CIPP evaluation model. Data collection was conducted through surveys, interviews, observations, and document analysis. The results of the study indicate that the strengthening program is effective in strengthening students' literacy and numeracy skills in general, aligned with school needs, supported by appropriate policies, and strengthened by the active involvement of stakeholders, especially principals and teachers. Investments in teacher training and the provision of facilities such as reading corners and numeracy materials have contributed to a more effective learning environment, despite minimal parental involvement. Literacy and numeracy activities are also supported by collaborative innovation and consistent monitoring by the relevant schools. The product evaluation also showed improvements in student competency, a more dynamic school literacy and numeracy culture, and increased publication of student and teacher work. The findings of this study have highlighted the importance of (1) careful planning of numeracy literacy strengthening programs, (2) ongoing professional development for teachers, (3) collaboration between stakeholders such as principals and parents, and (4) systematic evaluation to measure the effectiveness of literacy and numeracy strengthening programs in primary education.